A quality-of-life system to evaluate children with leukemia in China. Issue 36 (September 2018) - Wang, Zijuan; Mo, Lin; Jiang, Xiaoping; Liu, Yang; Shi, Lin
Abstract : Abstract: The scale for assessing the quality of life (QOL) of children with leukemia of different ages is vacant in China. Items for developing a QOL scale were selected through a literature review, interviews with 58 parents and children with leukemia by Delphi method, which involved pediatric oncologists, psychologists, and pediatricians. The initial items were formulated through 2 rounds of the Delphi method and statistical analyses. The formulated scale was pre-tested for reliability and validity. A method was adopted to weight the importance of items within the evaluation index system. The final scale includes 5 dimensions. There are 10 secondary items for age 2 to 4 years, 12 secondary items for all other age groups, and 29, 46, 52, and 50 tertiary items for the age groups 2 to 4 years, 5 to 7 years, 8 to 12 years, and 13 to 18 years, respectively. The authority coefficient for experts was 0.75, with Kendall's W coefficient P  < .01, for both rounds. The entire Cronbach alpha was >0.9, and the content validity >0.75. The weights of the first-grade items are: 0.201, 0.203, 0.198, 0.201, and 0.198. This quality-of-life scale for children with leukemia in China has demonstrated reliability and validity, while a further validity assessment is required. Abstract : Supplemental Digital Content is available in the text